Characteristics of boards of directors and board effectiveness: a study of Malaysian Public listed companies - Wan Yusoff, Wan Fauziah (2010)
Boards of directors are integral to modem corporations and, consequently, receive much attention from regulators, researchers and stakeholders. Although this domain is receiving increased scrutiny, most studies have been based on relating various dimensions of board structure and composition to fum financial performance. However, such studies have failed to draw an unambiguous conclusion about the impact of board structure and composition on firm performance. Considering the importance of board dynamics on the effectiveness of the board, this study examines the characteristics of members of boards of directors and determines the contribution that these characteristics make to the effectiveness of boards of directors in Malaysian Public Listed Companies (PLCs). Furthermore, there is limited study in this area from emerging-economy countries with relatively less developed capital markets. The underlying theme throughout this study is that characteristics of members of boards of directors are important components of board effectiveness. Based on extensive literature, this study develops a theoretical framework and six research questions. The characteristics of boards of director members considered in this study include demographic characteristics, personality characteristics and values, and competencies. Concerning the characteristics of effective boards, this study used a range of boards of directors' attributes including board roles, structure, composition, board membership and board dynamics. However, as this study utilised a qualitative approach, board effectiveness was assessed by reference to the pahcipants' points of view of their overall boards. In other words, what is being assessed in this study is not the relationship between board characteristics and fum financial performance but rather the participants perception of their boards. Data inthis study relied on two key sources: in-depth interviews and publicly available data from 2007 annual reports of the top 100 Malaysia PLCs. In-depth interviews were conducted with 33 directors of the top 100 Malaysian PLCs and 8 representatives of Malaysian corporate governance organisations. They were chosen because of their knowledge and experience in Malaysian corporate governance. The results of this study show that board members' demographic characteristics (age, tenure, multiple directorships), their personality characteristics and values (commitment, integrity, open mindedness, relationships with others) and their competencies (experience in corporate management, relevant knowledge and skills and relevant types of educational qualifications), as well as good networking with the government, are integral components of the effectiveness of Malaysian PLC boards. In addition, four components that have been found to be important for the effectiveness of Malayslan PLC boards include competence and diverse backgrounds of board members, a good culture, clear roles and responsibilities, and well-defined board strncturcs. More importantly, the results indicate that board membership is the most important component influencing board effectiveness for Malaysian PLCs. Although the relationship between board characteristics and fm performance has not been addressed directly, this study contributes to the understanding of the important characteristics of board members and board effectiveness. This thesis makes a number of contributions. The results add to the knowledge base for countries with developing economies. Further, it contributes to theory by proposing an integrated model of board effectiveness, which provides a basis for future hypothesis testing and theory building to identify more consistent relationships between the characteristics of boards of director members and fum performance. Testing the framework against f m s ' financial performance provides an avenue for future research that can contribute to closing the gap in the knowledge that exists concerning the relationship between board members' characteristics and firms' financial performance. In conclusion, the results from this thesis may have some implications for Malaysian regulators and others concerned with the establishment of guidelines pertaining to the selection of effective board members and effective boards.